Zinc-air fuel cell, a potential candidate for alternative energy - Sapkota, Prabal; Kim, Honggon (ELSEVIER SCIENCE INC, 2009)
A zinc-air fuel cell (ZAFC), which generates electricity by the reaction between oxygen and zinc pallets in a liquid alkaline electrolyte, is a potential candidate for an alternative energy generator. It is efficient, completely renewable, and cheap in fabrication because precious metal catalysts are not necessary. In addition, it is environmentally benign because of producing solely recyclable zinc oxide without gas emission. It is applicable to portable, mobile, stationary, and military purposes. In spite of its high potential as an alternative power source, it is yet in a preliminary stage of commercialization because of a few uncertainties remained. This paper reviews the present status of the ZAFC technology and the problems to be overcome for further advancement toward the potential next-generation alternative energy. (C) 2009 Published by Elsevier B.V. on behalf of The Korean Society of Industrial and Engineering Chemistry.
Keywords: CATALYST